Algebraic & geometric topology (Geometry & Topology Publications : Mathematics Institute, University of Warwick, 2001)
AGT is a fully refereed journal covering all of topology, understood broadly.
Keywords: Algebraic topology : Periodicals; Topologie algébrique : Périodiques; Algebraic topology; Geometry